2019
DOI: 10.1177/1461348419833868
|View full text |Cite
|
Sign up to set email alerts
|

On the Effectiveness of airborne infrasound in eliciting vestibular-evoked myogenic responses

Abstract: The use of airborne infrasound and other stimuli to elicit (cervical) vestibular-evoked myogenic potentials (cVEMPs) was studied to address the common proposition that infrasound may efficiently stimulate the vestibular system, an effect which may underlie the so-called wind-turbine syndrome. cVEMPs were measured for both ears of 15 normal-hearing subjects using three types of airborne sound stimulation: (1) 500-Hz tone bursts (transient); (2) 500-Hz sinusoidally amplitude-modulated tones at a 40-Hz rate (SAM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Stimulation of vestibular organs has been hypothesized to account for individuals complaining of motion sickness symptoms in response to infrasound emanating from wind farms in some sensitive individuals (Schomer et al, 2015). However, a recent study failed to measure responses of vestibular organs to airborne infrasound delivered through earphones (Jurado & Marquardt, 2019).…”
Section: (D) Neural Tuning In the Ascending Auditory Pathwaymentioning
confidence: 99%
“…Stimulation of vestibular organs has been hypothesized to account for individuals complaining of motion sickness symptoms in response to infrasound emanating from wind farms in some sensitive individuals (Schomer et al, 2015). However, a recent study failed to measure responses of vestibular organs to airborne infrasound delivered through earphones (Jurado & Marquardt, 2019).…”
Section: (D) Neural Tuning In the Ascending Auditory Pathwaymentioning
confidence: 99%
“…de Oliveira et al (2014) stated, qualitatively, that AMcVEMP amplitude increased with EMG activation. A fixed EMG activation range of 60-80 μV was used in one study (de Oliveira et al 2014), and other studies instructed participants to turn their head as far as was comfortable without reporting the amount of EMG activation or its relation to AMcVEMP amplitude (Bell et al 2010;Carnauba et al 2013;Jurado and Marquardt 2019). Existing AMcVEMP literature has not reported a systematic evaluation of the effects of EMG activation on AMcVEMP properties.…”
Section: Introductionmentioning
confidence: 99%
“…This perception may be caused by somatic sensation, as the chest resonances were estimated to be at 50 Hz 29 and a high correlation between the vibration at the chest and the perception of vibration was indicated in existing studies. 30 In addition, the vestibular system might play an important role since the health effects reported around low-frequency noise sources are quite similar to the equilibrium dysfunction; however, only a few studies [15][16][17] have examined the vestibular system.…”
Section: Discussionmentioning
confidence: 99%
“…110 dB at 40 Hz). 15 Similarly, animal studies have indicated that prolonged exposure to relatively low sound levels at low frequencies (e.g. 70 dB at 100 Hz for a month) causes damage to hair cells in the vestibular system.…”
Section: Introductionmentioning
confidence: 99%